ความสัมพันธ์ระหว่างปัจจัยส่วนบุคคล การได้รับการเสริมสร้างพลังอำนาจในงานแรงจูงใจใฝ่สัมฤทธิ์ กับความสุขในการทำงานของพยาบาลประจำการโรงพยาบาลมหาวิทยาลัยของรัฐ - จงจิต เลิศวิบูลย์มงคล (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
The purposes of this research were to study the level of work happiness of staff nurses, governmental university hospitals and to investigate relationships between personal factors, work empowerment, achievement motivation, and work happiness, governmental university hospitals. The research subjects were 375 staff nurses who were selected by multi-stage sampling. The research instruments were work empowerment, achievement motivation, and work happiness questionnaires. The content validity of the questionnaires were conducted. The reliability was tested by Cronbach{7f2019}s alpha coefficiencies, which were .92, .91, and .89, respectively. The data were analyzed by using percentage, mean, standard deviation, contingency coefficient, and Pearson{7f2019}s product moment correlation coefficients. Major findings were as follow: 1. Work happiness of staff nurses, governmental university hospitals was at the high level. 2. Personal factors of staff nurses in terms of age was positively significantly related to workhappiness, at the .05 level. Marital status was significantly related to work happiness. Educational level was not significantly related to work happiness of staff nurses. 3. There were positive significantly relationships between work empowerment, achievement motivation and work happiness of staff nurses, governmental university hospitals, at the .05 level (r = .514 and .570, respectively).